Model of Decision for the Management of Technology and Risk in a Port Community - Sepulveda-Salas, J; Duran-San Martin, C; Carrasco-Armijo, R (Growing Science, 2018)
Strategic management in a port system is complex since the Port Community has to coordinate actions and generate synergy among all the private actors that integrate the export and import logistics chains, trade associations and trade unions. Based on the opinion of the port experts and the analytical network process (ANP), the research identifies the relevant criteria for strategic, business and operational decision-making in the Port Community, in the technological and risk contexts. With the criteria found and considering the strategic alignment that is required, management indicators are constructed. Based on a generic model, a new strategic conceptual model (PORTGD) of ANP for decision management is designed for the Port Community, a cause and effect analysis is carried out and a sensitization study is performed on the nodes. The discussion of the results and conclusions highlights the importance of technological investment, control of port security and good practices for the port system investigated. © 2018 Growing Science Ltd. All rights reserved.